Reinhold Niebuhr and international relations theory realism beyond Thomas Hobbes - Pedro, Guilherme Marques (Routledge research in IR theory ;, 2018)
Guilherme Marques Pedro offers an innovative account of Reinhold Niebuhr's eclectic thought. This book offers an important contribution to IR scholarship, revealing the great historical wealth, intellectual originality but also the limitations and paradoxes of one of the greatest American political thinkers of the twentieth century.